Phytoliths, parasites, fibers, and feathers from dental calculus and sediment from Iron Age Luistari cemetery, Finland. (15th October 2019) - Juhola, Tytti; Henry, Amanda G.; Kirkinen, Tuija; Laakkonen, Juha; Väliranta, Minna
Abstract: Our understanding of subsistence strategies, resources and lifeways of Finnish Iron Age populations remains incomplete despite archaeological, osteological, macrobotanical, and palynological investigations. This is due in part to poor preservation of organic macroremains in the acidic boreal sediments. To address this problem, here we present the first data from microscopic remains preserved in prehistoric dental calculus from Finland. We extracted and analysed both plant and animal microremains from human calculus and burial site sediment samples, originating from Luistari cemetery in southwestern Finland (samples from c. 600–1200 calAD). We recovered phytoliths, parasites, fibers and feathers. While in Finland few previous archaeological studies have investigated phytoliths, our study confirms the importance of these microremains for interpretating dietary patterns. It is also the first time that intestinal parasites have been reported in Finland. Our study demonstrates that, especially when working with acidic sediments typical for boreal environments, microremain studies can considerably increase the information value of archaeological samples, and that dental calculus and phytolith analysis are important new methods in the research of prehistorical lifestyles. This combined microremain analysis should be more broadly applied in contexts where other dietary records do not remain. Highlights: Microremain analysis proved to be especially valuable in an acidic boreal context. Remains in dental calculus and sediment provided dietary and behavioral information. Late Iron Age people in Finland ate grass grains and processed bast fibers. They also exploited furs and feathers and suffered from intestinal parasites.